Structural diversity, gas adsorption and magnetic properties of three coordination polymers based on a rigid multicarboxylate ligand. Issue 42 (8th October 2020) - Gao, Lingling; Bian, Yongjun; Tian, Yuan; Chen, Yongqiang; Hu, Tuoping
Abstract : A pictogram: the gas adsorption and magnetic properties of three Co(ii ) coordination polymers constructed from 3, 5-di(2′, 5′-dicarboxylphenyl)benzoic acid ligand have been explored. Abstract : Three Co(ii ) coordination polymers (CPs), {[Co2 (HL)(1, 4-bibb)(H2 O)]·(CH3 CN)·(H2 O)} n (1 ), {[Co4 (L)(OH)3 (H2 O)4 ]·(1, 4-bmib)} n (2 ) and {[Co6 (L)2 (OH)2 (4, 4-biyb)]·(CH3 CN)·(H2 O)} n (3 ) have been obtained based on a V-shaped rigid pentacarboxylate ligand (H5 L = 3, 5-di(2′, 5′-dicarboxylphenyl)benzoic acid) and different N-donor ligands. All complexes show 3D structures and contain open carboxyl sites and "accessible metal sites" (AMSs). The gas adsorption experiments show that 1 and 3 have a high H2 adsorption capacity at 77 K and in particular, 3 displays the selective uptake of CO2 over CH4 (14.2 for CO2 /CH4 = 0.5/0.5 and 11.0 for CO2 /CH4 = 0.05/0.95 under 1 bar at 298 K). Furthermore, anti-ferromagnetic interactions among Co(ii ) ions are observed in 2 .